PENGARUH RANGE OF MOTION (ROM) DAN MIRROR THERAPY TERHADAP KEKUATAN OTOT PADA LANSIA DENGAN STROKE DI POSYANDU LANSIA DI SLEMAN - Ignasia Nila Siwi; Rianto, Ignasia Nila Siwi (Sekolah Tinggi Ilmu Kesehatan Madani Yogyakarta, 2025)
Stroke is a condition in which blood flow to the brain is disrupted, resulting in muscle weakness that limits the daily functional abilities of older adults. Non-pharmacological therapies such as Range of Motion (ROM) and Mirror Therapy play an important role in stroke rehabilitation. This study aimed to examine the effect of ROM and Mirror Therapy on improving muscle strength among older adults with stroke. A quantitative quasi-experimental design with a pre-test–post-test control group was used. A total of 21 participants were divided into two groups: 11 participants in the experimental group received both ROM and Mirror Therapy, while 10 participants in the control group received only ROM therapy. Muscle strength was measured using the Manual Muscle Testing (MMT) instrument. Data were analyzed using the Wilcoxon Signed-Rank Test, Paired Samples T-Test, and Mann–Whitney Test. The Wilcoxon test in the experimental group showed a significant increase in muscle strength (p = 0.005). The Mann–Whitney test revealed a significant difference between the post-test results of the control and experimental groups (p = 0.014), with the experimental group showing a higher mean score. The findings indicate that the combination of Range of Motion (ROM) and Mirror Therapy significantly improves muscle strength in older adults with stroke.